„Granma" i „El Nuevo Herald" - kubańska wojna propagandowa przed wyborami prezydenckimi w USA w 2004 roku - Radosław Sajna (Świat Idei i Polityki, 2005)
Since the beginning of its existence, i.e. 1965, the Cuban daily "Granma" has been used as a propaganda tube for Fidel Castro's regime. The Cuban opposition, deprived of a possibility of speaking in the public media, had to express their opinions outside the island. Most dissidents settled on the nearby Florida, where "El Nuevo Herald" started to be issued, speaking out on the matters important for Cuba. At first, the newspaper was a Spanish supplement to the American daily "The Miami Herald", and since 1988 it has been a separate title. Before the presidential election in the United States, both "Granma" and "El Nuevo Herald" used to clash in all possible aspects. The "Granma" criticized George Bush to the bitter end, while the "El Nuevo Herald" supported his tendency toward the re-election to the post of the US president. The Cuban daily was in favor of the revolution in Venezuela, which irritated the Miami publicists. The "El Nuevo Herald", in the article by Pablo Alfonso, wrote about economic nonsense of the Cuban authorities, and the "Granma" described ominous intentions of Americans to Iraq. The basis of the conflict was still a vision of Cuba's development - Castro's communism or pro-American capitalism?